Embolization of Ruptured Renal Angiomyolipoma in Puerpera - Góes Junior, Adenauer Marinho de Oliveira; Jeha, Salim Abdon Haber; de Oliveira, Carolina Pinheiro; Santos, Daniel Arthur Santos dos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Angiomyolipomas (AMLs) are rare benign tumors derived from mesenchymal tissue and composed of varying degrees of adipose tissue, muscle and blood vessels. Renal AMLs (RAMLs) are the result of a sporadic event, and, in most of cases, the diagnosis is usually incidental, but hemorrhage and shock may be present. During pregnancy, the size of AMLs may increase and they may rupture, probably due to the high expression of hormone receptors, and the increase in maternal circulation and abdominal pressure. The authors present a case of a woman with ruptured RAML submitted to urgent endovascular treatment four days after giving birth by cesarean section.
Keywords: angiomyolipoma; kidney; therapeutic embolization; pregnancy complications; postpartum period